Natural radioactivity contents in bottled mineral water using gamma spectroscopy - Siti Alrina Zainal Rain Rancis, 1990-; Suhairul Hashim, supervisor; Fakulti Sains (2012)
Project Paper Sarjana Muda Sains (Fizik Kesihatan)) - Universiti Teknologi Malaysia, 2012